[Comment] Compara tive effectiveness of bevacizumab versus cetuximab in meta static colorectal cancer patients without primary tumor resec tion - Li Yingru; Li Shaotang (结直肠肛门外科)
Primary tumor resection may be unfeasible in metastatic colorectal cancer. We determined the effects of bevacizumab and cetuximab therapies on survival or conversion surgery in patients with metastatic colorectal cancer who did not undergo primary tumor resection. This retrospective cohort study enrolled 8466 patients who underwent first-line bevacizumab- or cetuximab-based therapy. We analyzed the data of both therapies in patients who did not undergo primary tumor resection. Overall survival after targeted therapy plus chemotherapy was assessed. The groups were matched using propensity score matching and weighting. Cetuximab resulted in lower mortality than bevacizumab (hazard ratio (HR) = 0.75); however, it did not have the same effect in patients that underwent primary tumor resection (HR = 0.95) after propensity score weighting. Among patients treated with targeted agents, primary tumor resection was associated with lower mortality among those who received both bevacizumab (HR = 0.60) and cetuximab (HR = 0.75). Among patients that did not undergo primary tumor resection, multivariable analysis for conversion surgery showed that the cetuximab group (HR = 1.82) had a significantly higher metastasectomy rate. In these patients, cetuximab-based therapy was associated with significantly better survival compared with bevacizumab-based therapy. Cetuximab also yielded a higher conversion surgery rate. These findings demonstrate the importance of stratification by primary tumor resection in the application of current treatment guidelines and initiation of future clinical trials.